To find \( f(g(x)) \), you need to substitute \( g(x) \) into \( f(x) \).
Given:
- \( f(x) = 12x \)
- \( g(x) = \frac{x}{12} \)
Now, let's find \( f(g(x)) \):
-
Substitute \( g(x) \) into \( f(x) \): \[ f(g(x)) = f\left(\frac{x}{12}\right) \]
-
Now, apply the function \( f \) to \( \frac{x}{12} \): \[ f\left(\frac{x}{12}\right) = 12 \left(\frac{x}{12}\right) \]
-
Simplify: \[ f\left(\frac{x}{12}\right) = \frac{12x}{12} = x \]
So, \[ f(g(x)) = x \]
Part 1 Answer:
\( f(g(x)) = x \)
Part 2
Now let's find \( g(f(x)) \):
-
Substitute \( f(x) \) into \( g(x) \): \[ g(f(x)) = g(12x) \]
-
Now, apply the function \( g \) to \( 12x \): \[ g(12x) = \frac{12x}{12} \]
-
Simplify: \[ g(12x) = x \]
So, \[ g(f(x)) = x \]
Part 2 Answer:
\( g(f(x)) = x \)
Part 3
Since both \( f(g(x)) = x \) and \( g(f(x)) = x \), we can conclude that the functions \( f(x) \) and \( g(x) \) are indeed inverse functions of each other.
Part 3 Conclusion:
Yes, \( f \) and \( g \) are inverses of each other.